Effect of kimchi intake on body weight of general community dwellers: a prospective cohort study. Issue 4 (8th February 2023) - Tan, Li-Juan; Yun, Ye-Rang; Hong, Sung Wook; Shin, Sangah
Abstract : Long-term moderate kimchi intake (about 2–3 servings per day), mainly of baechu (cabbage) kimchi, was associated with weight loss in middle-aged and older Koreans, especially men. Abstract : The impact of kimchi intake on weight management has been a topic of interest. We aimed to conduct an epidemiological study to investigate the association between kimchi intake and weight loss. Participants were selected from the Health Examinees cohort study. Kimchi intake was assessed by a 106-item semi-quantitative food frequency questionnaire, including four types of kimchi. Obesity was defined according to the Korean Society for the Study of Obesity guidelines. We performed a correlation analysis among all participants ( N = 58 290) and conducted a prospective risk assessment analysis among participants with a baseline BMI value ≥25 kg m −2 ( N = 20 066). In the correlation analysis, higher kimchi consumption was found to be associated with a lower increment in BMI change (men, β 0.169, 95% CI (0.025, 0.313); women, β 0.140, 95% CI (0.046, 0.236)) compared with the lower group. The risk assessment analysis indicated that moderate kimchi consumption is associated with normal weight development in men (Q3, hazard ratio, 1.28, 95% CI (1.06, 1.54)). Baechu [cabbage] kimchi intake also showed a significant association among men participants (all p for trend <0.05). In conclusion, moderate kimchi intake was associated with weight loss among middle-aged and older Koreans, especially in men.